Pigmentary Mosaicism: An Overview - C. Colmant; E. Legius; N. Cattaert; M.‐A. Morren (JEADV Clinical Practice)
ABSTRACT Mosaicism refers to an individual who developed from a single fertilised egg but has two or more populations of cells with a different genotype as a result of a postzygotic mutation. Pigmentary mosaicism is reflected by a patterned hypo‐, hyperpigmentation, or both combined in cutis tricolour. Pigmentary mosaicism can be associated with extracutaneous features (mainly neurological, musculoskeletal or ophthalmological). Three main mechanisms are involved in the development of pigmentary mosaicism: mosaicism for a chromosomal abnormality, mosaicism for an intragenic pathogenic variant and epigenetic mosaicism (X‐linked due to X‐chromosome inactivation). Recently, different new disease entities have been described with a specific genotype, most of them with characteristic extra‐cutaneous features.